Genes Associated with Calcium Signaling are Involved in Alcohol‐Induced Breast Cancer Growth. (26th December 2020) - Ho, Charles; Lin, Chin‐Yo
Abstract : Background: Alcohol consumption is a risk factor for breast cancer, contributing to up to nearly 23, 000 new cases each year. Mechanistic studies show that alcohol increases tumor aggressiveness and metastatic potential, promotes angiogenesis, induces chronic inflammation, and dysregulates RNA polymerase III–related genes. Alcohol has also been shown to affect estrogen signaling in breast cancer, including in our study of the transcriptomic effects of alcohol in breast cancer cells. Methods: To elucidate mechanisms of action of alcohol in breast cancer, we carried out secondary analyses of our alcohol‐responsive transcriptome data using gene ontology and pathway databases and analysis tools and cistromic data analysis of candidate transcription factors which may mediate the transcriptomic alterations. Predicted alcohol‐responsive pathways and mechanisms were perturbed and examined experimentally in breast cancer cells. The clinical relevance of identified genes was determined by expression profiles in patient samples and correlation with disease outcomes and alcohol consumption in previously published study cohorts. Results: Gene ontology analysis showed that alcohol alters the expression of many metabolism‐related genes, and cistromic data of differentially expressed genes revealed the potential involvement of nuclear factor of activated T cells 3 ( NFATC3 ) in mediating the transcriptomic effects of alcohol. Pathway analysis also predicted regulation of calcium signaling by alcohol in breast cancer cells. Chemical perturbation of this pathway reversed the effect of alcohol on breast cancer cell growth and reduced the elevated cytosolic Ca 2+ levels induced by alcohol. Expression levels of alcohol‐responsive genes in tumor samples from breast cancer patients are associated with poor disease outcomes. Moreover, expression of some of these genes was altered in breast cancer patients who consumed alcohol previously as compared to those who did not drink. Conclusion: Alcohol alters expression of genes that regulate intracellular calcium levels and downstream signaling pathways which drive breast cancer cell proliferation and disease progression. Abstract : Exposure of breast cancer cells to alcohol alters the expression of genes which regulate intracellular calcium ion levels and also those involved in mediating the effects of calcium signaling on cancer‐related processes. Moreover, expression profiles of these genes in clinical samples are associated with disease outcomes and survival of breast cancer patients. Interestingly, some of these genes have also been reported to be differentially expressed in animal models of alcoholism, suggestive of common mechanisms across end organs of alcohol consumption.